Improving Micro, Small and Medium Enterprises' Understanding of Istishna Accounting through Mentoring Activities - Rizkyaningrum, Adinda Agustinayu; Lestari, Lisa Yuni; Febrianto, M. Nanang; Luknawati, Erra Fitri; Asiyah, Binti Nur (Journal of Community Service and Society Empowerment, 2025)
Financial bookkeeping plays an important role to determine the financial condition in one transaction period. Financial bookkeeping that is carried out systematically, referring to accounting, can improve transparency, financial control and decision making, especially Sharia accounting bookkeeping. However, the level of Islamic financial literacy of small and micro businesses is still low. This assistance is a form of increasing the understanding of micro, small and medium enterprises about financial bookkeeping through Istishna accounting. Assistance was carried out in 3 businesses, namely the Cikra Pecel chili business, the brick press business and the Sanma Bouquet business, which was carried out through interviews and service learning on May 3, 2025. The results obtained that in the pre-implementation stage, the three businesses had simple bookkeeping that was not systematic and did not recognize the Istishna accounting contract and bookkeeping. The implementation stage was carried out by providing material for the introduction of Istishna accounting contracts and bookkeeping. At the third post-implementation stage, the three business actors gained understanding and knowledge that was not just theory but also the practice of journaling and determining business profits and losses. The evaluation results show that further mentoring activities are needed to strengthen the understanding and consistency of Sharia accounting bookkeeping practices for MSMEs on a regular basis.